Graphene based-coating effective ways of preventing corrosion - Siti Maznah, Kabeb; Azman, Hassan; Zurina, Mohamad (Penerbit UMP, 2021)
This book is the culmination of nearly four years of work I have done on epoxy-based nanocomposite coatings. Honestly, I could not produce this book without a strong support group especially from my family and committed team. I have completed my doctorate study successfully with flying colour after went through many obstacles and difficulties. I succeed to complete my doctorate study with flying colors. This book contains comprehensive information about the recent development of epoxy nanocomposite coating, property relationships, and its applications. A corrosion prevention method with a detailed explanation on the mechanism of anti-corrosion coatings has been inclusively discussed. The detailed description of graphene-based coatings with ample research findings has been thoroughly deliberated. A more in-depth study on the effect of graphenebased nanofillers on anticorrosion performance is highlighted and successfully proved through scientific evidence. I hope that this book will be valued and appreciated by students and researchers from the same field of studies